Indications for intestinal transplantation: recognizing the scope and limits of total parenteral nutrition - Gotthardt, Daniel; Gauss, Annika; Zech, Ulrike; Mehrabi, Arianeb; Weiss, Karl Heinz; Sauer, Peter; Stremmel, Wolfgang; Büchler, Markus W.; Schemmer, Peter (Clinical transplantation. Supplement, 2013)
Total parenteral nutrition (TPN) is currently the treatment of choice for patients with intestinal failure. Intestinal failure in adults is mostly due to short bowel syndrome, which is most often caused by ischemia and Crohn's disease. However, TPN fails in a substantial number of cases. For patients with TPN failure, intestinal transplantation (ITx) may be offered as a treatment. TPN failure is considered to be present either if nutrition itself is not possible or if complications of TPN occur. These complications can, for example, originate from recurrent line infections or thrombosis. As TPN is usually a lifelong therapy and is associated with substantial impairment of the quality of life, the tolerance of each patient to this procedure is another important consideration in the decision making about whether to perform transplantation. The survival rates of intestinal transplant recipients have now reached the same level as that of recipients of other solid organ transplants. A five-yr survival of up to 80% has been reported in specialized centers, whereas registry data show rates of <80%. Although in about one-third of patients, isolated ITx is sufficient, patients with concurrent liver disease (mostly due to TPN) benefit from combined intestinal and liver transplantation. In some cases, multivisceral transplantation is necessary. Here, we review the current indications for ITx with a special focus on TPN.
Gesehen am 05.03.2021